Pengaruh Komisaris Independen dan Investment Opportunity Set (IOS) terhadap Kinerja Perusahaan - Rivai, Fayyadh Erdy; Mulyani, Erly (Universitas Negeri Padang, 2024)
The purpose of this study is to examine the impact of independent commissioners and investment opportunity set on firm performance. Firm performance, which is assessed by net income divided by equity, is the dependent variable. Meanwhile, independent commissioners are measured by the number of independent commissioners divided by the number of commissioners. Companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022 constitute the study population. Purposive sampling was used to determine the research sample, and 18 companies with a total of 90 observations were obtained. Multiple linear regression analysis was used as the analysis technique. Based on the results of this study, independent commissioners have a positive effect on company performance, but investment opportunity set has a negative effect on company performance.